2015
DOI: 10.1152/ajpendo.00312.2014
|View full text |Cite
|
Sign up to set email alerts
|

Leptin in pregnancy and development: a contributor to adulthood disease?

Abstract: Emerging research has highlighted the importance of leptin in fetal growth and development independent of its essential role in the maintenance of hunger and satiety through the modulation of neuropeptide Y and proopiomelanocortin neurons. Alterations in maternal-placental-fetal leptin exchange may modify the development of the fetus and contribute to the increased risk of developing disease in adulthood. In addition, leptin also plays an important role in reproductive functions, with plasma leptin concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
93
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(99 citation statements)
references
References 163 publications
1
93
0
5
Order By: Relevance
“…Leptin deficiency with the loss of placental derived leptin in growth restricted and pre-term delivered offspring contributes to reduced frontal cortex volume and behavioral deficits in rats (Dexter et al 2014). Leptin is believed to impact fetal organ growth, including the brain, appetite regulation, and cognition during early development (Briffa et al 2015). Some authors have suggested that leptin replacement in early life may improve long-term metabolic and behavioral outcomes (Meyer et al 2014; Chen et al 2011).…”
Section: Long-term Outcomes Of Children Born To Obese Mothersmentioning
confidence: 99%
“…Leptin deficiency with the loss of placental derived leptin in growth restricted and pre-term delivered offspring contributes to reduced frontal cortex volume and behavioral deficits in rats (Dexter et al 2014). Leptin is believed to impact fetal organ growth, including the brain, appetite regulation, and cognition during early development (Briffa et al 2015). Some authors have suggested that leptin replacement in early life may improve long-term metabolic and behavioral outcomes (Meyer et al 2014; Chen et al 2011).…”
Section: Long-term Outcomes Of Children Born To Obese Mothersmentioning
confidence: 99%
“…Encoded by the ob gene, leptin is a peptide hormone produced by adipocytes that has anorexigenic effects upon appetite (Myers et al, 2008). In addition, leptin has well-described effects upon immune function (reviewed by Carlton et al, 2012), reproduction (Caprio et al, 2001; Tena-Sempere, 2007), and development (Briffa et al, 2015; Crespi and Unkefer, 2014). In mammals, experimental reductions in white adipose tissue via surgical removal (i.e., lipectomy) of specific white adipose tissue depots impairs antibody production; immune function is restored following compensatory regrowth of the remaining fat pads (Demas et al, 2003).…”
Section: Energetic Signals and Immunitymentioning
confidence: 99%
“…Umbilical cord leptin levels are elevated in obese pregnancies (Ferretti et al, 2014;Karakosta et al, 2013;Walsh et al, 2014) and neonatal circulating leptin is elevated in offspring of obese mice (Samuelsson et al, 2008). Therefore, early life hyperleptinaemia may drive sympathetic hyperstimulation in the developing renal-cardiovascular system, leading to hypertension and cardiovascular dysfunction in adulthood (Briffa et al, 2014). Indeed, neonatal leptin administration in rats results in cardiac hypertrophy and dysfunction in adulthood (Marques et al, 2014b).…”
Section: Cardiovascular Systemmentioning
confidence: 99%